Perch shape and material affect perch use and health parameters of laying hens during the rearing and laying phase - Ariane Stratmann; Nadine Ringgenberg (Journal of Applied Poultry Research)
SUMMARY: Perches are an important resource for laying hens and differ in characteristics like shape, material and diameter. In this study, different perches were tested in regard to animal welfare, focusing specifically on the behavior and health of laying hens during rearing and lay. Five perches, i.e., square-fiber, mushroom-metal, mushroom-plastic, round-plastic and round-metal perches, were installed in 15 experimental pens with 1 perch type per pen. Each pen was populated with 20 hens (10 Lohmann Selected Leghorn and 10 Lohmann Brown hens) and kept in the same pen from d 1 until 40 wk of age. Different behaviors and health parameters (i.e., keel, footpad and plumage condition) were assessed at various ages by scan sampling and continuous observations of video recordings and live assessments, respectively. Perch use was affected by age, hybrid and perch type: it increased with age, white birds used perches more than brown birds, the round-metal perch was used the least and the mushroom-metal perch the most. In more than 50% of observed walking bouts on perches, balance movements occurred. These were observed more during the dusk phase and on the mushroom-shaped perches while birds with the round-metal perch had the least balance problems but also the least number of walking bouts. All health parameters were of minor severity. They were however influenced by perch type and age, where all of them increased with age and in birds with mushroom-metal perches. Hen behavior and health were affected by perch type, highlighting its significance for laying hen welfare.